Efeitos territoriais da apropriação do cerrado pelo agronegócio na comunidade Araras – Morrinhos (GO) - Morais, Débora Rosa de (2017)
The Brazilian countryside has undergone intense transformations since the 1970s, due to the modernization agriculture process. In this research, this process is understood through the effects of the appropriation of the Cerrado by agribusiness, and the transformations in the territory of Araras rural community. The Goiás state and, consequently, the city of Morrinhos, experienced the expansion of agricultural modernization, occurring in an uneven manner. The city of Morrinhos (GO) and the Araras rural community have stamped in their history the dynamism of the occupation process of the Cerrado from agribusiness. On one side peasant farmers struggling to stay on their land. Carrying out the activities of cattle management and small bovine milk production, conditioned to the interests of the Mixed Cooperative from Milk Producers of Morrinhos (Complem). In the other, the economic growth generated by this model of highly- skilled agriculture that serves industries, in addition to grain production, sugar cane, energy, among other products. Bibliographical, documentary and field research were used, with structured interviews, semistructured interviews, observation, notes in the field book and photographic records. Because of these situations the present work deals with the contradictions inherent to the production model, with the concentration of investments in an uneven manner, presenting strong deficiencies, as it happens in the rural community surveyed. It is proposed to understand the main characteristics of peasant agriculture and agribusiness inserted in Araras and the main environmental impacts that result from the process of use of the cerrado occupation.